A prospective audit against national standards of the presentation and management of acute pancreatitis in the South of England. Issue 2 (1st February 2000) - Toh, S K C; Phillips, S; Johnson, C D
Abstract : BACKGROUND: The incidence of acute pancreatitis shows regional variations in the UK. AIMS: To document the incidence and presentation of acute pancreatitis in hospitals in Wessex, and to audit the process and outcome of management of patients against the UK guidelines. METHODS: A prospective survey was carried out of all patients with acute pancreatitis in a one year period, in eight geographically adjacent acute hospitals in the Wessex region. RESULTS: 186 patients with acute pancreatitis were identified, an incidence of 152 per million in the adult population. Aetiology was: gallstones 33%, alcohol 20%, idiopathic 32%, other 15%. There were 60 severe cases with 17 deaths. Age and APACHE-II score had significant relations to outcome, but delay to admission, serum amylase level, aetiology, and sex did not. The mortality rate (9.1%) was within the audit standard of 10%. Some management goals were not met: in mild cases, only one third of patients with gallstone pancreatitis had definitive treatment within four weeks. In severe cases, there was poor use of objective severity stratification (19%), low admission rates to a high dependency unit or intensive care unit (67%), and only 33% of patients had computed tomography. Only seven of 17 patients with severe gallstone pancreatitis had an urgent endoscopic retrograde cholangiopancreatography. CONCLUSIONS: The incidence of clinically diagnosed acute pancreatitis in England continues to rise. Current management of acute pancreatitis is suboptimal when compared with evidence based UK guidelines but the mortality rate was within the guideline standard.